Anticipatory action for drought in the Sahel: an innovation for drought risk management or a buzzword? - Parodi, Luca Sergio Italo; Enenkel, Markus; Lombardi, Niccolò; Ngaina, Joshua (Frontiers in Climate, 2024)
Anticipatory action is an approach that combines early warning information with flexible, pre-positioned funds to trigger actions that mitigate the impact of predictable shocks on the most vulnerable people. Historically, drought is the climatic hazard that led to the highest and most severe humanitarian impacts in the Sahel. This region, according to climate projections, will be one of the most deeply affected by climate change in future years, leading to considerable changes to societies, economies, as well as impacting rural communities. While this negative projection may lead to further increases in humanitarian consequences, recent experiences from integrating anticipatory action for drought into humanitarian practice hold positive prospects. This article will review current experiences on anticipatory action for drought in the Sahel and shed light on whether this approach has brought innovation in local disaster risk management. Through the review of recent initiatives in Burkina Faso, Chad and Niger, this paper highlights key advancements as well as gaps and challenges pertaining to key components of anticipatory action and disaster risk management, namely: 1) data, risk analysis and early warning; 2) funding; 3) preparedness and community engagement; 4) learning, coordination and partnership; 5) policies and institutional frameworks. Even in challenging environments like in the Sahel, anticipatory action for drought can become an integral component of standard disaster risk management and financing strategies. However, this process will require more robust evidence about which ingredients of anticipatory action approaches lead to the desired result.